Isotopi Dalam Kumpulan Puisi Aku Ini Binatang Jalang Karya Chairil Anwar: Kajian Analisis Wacana - Pelangi, Inne (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
Indonesia, as a country with diverse ethnicities and cultures, requires effective communication tools to This research aims to describe the isotopes found in the Poetry Collection "Aku Ini Binatang Jalang" by Chairil Anwar. The benefits of this research are: (1) To increase the researcher's insight and knowledge in understanding isotopes in the Poetry Collection "Aku Ini Binatang Jalang" by Chairil Anwar. (2) To increase the researcher's insight and knowledge regarding discourse analysis, particularly on the lexical cohesion of isotopes. (3) To provide knowledge to readers regarding isotopes in the Poetry Collection "Aku Ini Binatang Jalang" by Chairil Anwar. (4) To increase knowledge for those involved in the field of language regarding isotopes. (5) As a reference or resource for further research. This research uses a qualitative research method. Furthermore, the techniques used in data collection in this research are reading techniques and documentation techniques. The types of data used in this research consist of primary and secondary data. The data source in this research is derived from the Poetry Collection "Aku Ini Binatang Jalang" by Chairil Anwar, published by PT Gramedia Pustaka Umum with a book thickness of 111 pages. The results of this research indicate that the isotopes found in Chairil Anwar's Poetry Collection include sound isotopes, nature isotopes, number isotopes, life isotopes, place isotopes, heat isotopes, size isotopes, quantity isotopes, garden isotopes, nature isotopes, and natural isotopes.